2011
DOI: 10.1002/aenm.201100143
|View full text |Cite
|
Sign up to set email alerts
|

Direct Evaluation of Intrinsic Optoelectronic Performance of Organic Photovoltaic Cells with Minimizing Impurity and Degradation Effects

Abstract: A correlation between the photovoltaic performance and dynamics of transient photoconductivity is investigated by fl ash-photolysis time-resolved microwave conductivity (FP-TRMC). This electrode-less technique offers chances to mitigate barriers for direct, speedy, and robust evaluation of bulk heterojunction (BHJ) fi lm. We examined the blend ratio, process (solvent and thermal annealing), and impurity (a metal complex of Pd) and degradation effects in BHJ fi lms consisting of poly(3-hexylthiophene) (P3HT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 108 publications
6
96
0
Order By: Relevance
“…Several studies have previously demonstrated that P3HT molecular weight variations in the range of 10-20 kg mol À 1 do not significantly affect the morphology and device performance of the pristine polymer or P3HT/PCBM-based photovoltaics [22][23][24] . In addition, the Ni residues in the highly pure protonated and deuterated P3HT polymers synthesized for this study were measured by inductively coupled plasma mass spectroscopy to be less than 0.0014 wt.%, which is 50 times smaller than the threshold concentration of metal impurities for noticeable effects on device performance in previous studies [25][26][27] . Therefore, we exclude the impact of the molecular weight difference and metal residues on the measured optoelectronic properties between the deuterated and protonated P3HT polymers in this work.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have previously demonstrated that P3HT molecular weight variations in the range of 10-20 kg mol À 1 do not significantly affect the morphology and device performance of the pristine polymer or P3HT/PCBM-based photovoltaics [22][23][24] . In addition, the Ni residues in the highly pure protonated and deuterated P3HT polymers synthesized for this study were measured by inductively coupled plasma mass spectroscopy to be less than 0.0014 wt.%, which is 50 times smaller than the threshold concentration of metal impurities for noticeable effects on device performance in previous studies [25][26][27] . Therefore, we exclude the impact of the molecular weight difference and metal residues on the measured optoelectronic properties between the deuterated and protonated P3HT polymers in this work.…”
Section: Resultsmentioning
confidence: 99%
“…This is assumed due to an essential role of electron delocalization in PCBM aggregates for efficient charge separation. In the case of crystalline polymers such as poly(3-hexylthiophene) 33,34) and high performing LBPs, 35) the 1:1 blend ratio (50 wt%) is often optimal, because self-assembling nature of polymer concurrently promotes the growth of PCBM aggregates. In the present case, BTT-TP is amorphous, while BTT-FT and BTT-NTz are more crystalline, as evidenced by X-ray diffraction (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…C 60 has a very weak fluorescence at ca. 700 nm, 32) as a result of symmetrically forbidden transition from the excited singlet state to ground state.…”
Section: Resultsmentioning
confidence: 99%